2014
DOI: 10.1155/2014/212864
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes, Antibiotic Resistance, and ST-8 Genetic Clone inCampylobacterIsolates from Sheep and Goats in Grenada

Abstract: Rectal swabs from 155 sheep and 252 goats from Grenada were evaluated to determine the prevalence of Campylobacter spp., antibiotic resistance, and multilocus sequence types. Fifteen Campylobacter isolates were obtained (14 C. jejuni and 1 C. coli). The prevalence (3.7%) did not differ significantly between sheep (4.5%) and goats (3.2%). Among the seven antimicrobials tested, resistance was only detected for tetracycline (30.8%) and metronidazole (38.5%). Campylobacter isolates showed no significant difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
6
2
Order By: Relevance
“…Other studies in different geographical areas have also shown a low resistance rate of Campylobacter isolates from different animals and humans to tetracycline in comparison with our observation (Moore et al, 2006;Kashoma et al, 2015). On the other hand, other studies have reported high resistance rates of Campylobacter isolates from animals and humans to tetracycline, which is in close agreement with the observation in this study (Hariharan et al, 1990;Rollo et al, 2010;Scott et al, 2012;Stone et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other studies in different geographical areas have also shown a low resistance rate of Campylobacter isolates from different animals and humans to tetracycline in comparison with our observation (Moore et al, 2006;Kashoma et al, 2015). On the other hand, other studies have reported high resistance rates of Campylobacter isolates from animals and humans to tetracycline, which is in close agreement with the observation in this study (Hariharan et al, 1990;Rollo et al, 2010;Scott et al, 2012;Stone et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…The high frequency of tetracycline resistance (61.6%) observed in this study differed significantly ( p < 0.001) from the resistance to tetracycline (19.6%, 10/51) observed in poultry by Stone et al (2013). Another study on sheep and goats in Grenada by Stone et al (2014) revealed resistance of Campylobacter isolates to tetracycline (30.8%, 4/13), which is also significantly lower ( p = 0.005) than the observation in this study. Other studies in different geographical areas have also shown a low resistance rate of Campylobacter isolates from different animals and humans to tetracycline in comparison with our observation (Moore et al, 2006;Kashoma et al, 2015).…”
Section: Discussioncontrasting
confidence: 69%
“…This clone is a predominant cause of Campylobacterassociated ovine abortions and is also distributed in feedlot and dairy cattle in the United States (23,35). A recent study also reported identification of clone SA in Grenada (36). The lack of clone SA detection in this study is not entirely surprising, as we have previously found that the distribution of clone SA is highly variable from farm to farm (25).…”
Section: Discussionsupporting
confidence: 59%
“…The 18.6% Campylobacter prevalence in sheep faeces is lower than the 23% and 38.0% rates reported in studies in Ghana and Ethiopia, respectively [ 17 , 22 ], but higher than the 4.5% reported in USA [ 23 ]. In sheep carcasses, rates of 11.0% have been reported in Ethiopia which is lower than the 35.9% obtained in this study although a higher rate of 72.2% has been described in Greece [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 61%